China's international roles: challenging or supporting international order? - Harnisch, Sebastian; Bersick, Sebastian; Gottwald, Jörn-Carsten (Role theory and international relations, 2016)
Role theory and the study of Chinese foreign policy / Sebastian Harnisch -- Historical narrative, remembrance, and the ordering of the world : a historical assessment of China's international relations / Bart Dessein -- China's historical self and its international role / Sebastian Harnisch -- The identity and international role of China : relational grand strategy / Chih-Yu Shih, Chiung-Chiu Huang -- Philosophy, identity and role theory with "Chinese characteristics" / Chen Yudan -- The United States' and China : altercast roles and changing power in the twentieth century / Cameron G. Thies -- China's role in the transformation of international system / Chen Yugang -- China's role in international institutions : the case of global economic governance / Jörn-Carsten Gottwald -- Finding a new role in East Asian financial order : China's hesitant turn towards leadership / Mikko Huotari -- China and socialist countries : role change and role continuity / Nele Noesselt -- China and Japan : partner, rival and enemy? / Sebastian Maslow -- China's changing role in its all-weather friendship with Africa / Niall Duggan -- China and the EU : trade and national role conceptions / Sebastian Bersick -- Conclusion : China's role evolution : domestic imperatives and foreign expectations / Sebastian Harnisch, Sebastian Bersick, Jörn-Carsten Gottwald